2006
DOI: 10.1346/ccmn.2006.0540308
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Heating on the Surface Area, Porosity and Surface Acidity of a Bentonite

Abstract: The Hançılı bentonite from Turkey shows significant changes in surface area, micro- and mesoporosity, surface acidity and acid strength with heating from 100 to 900°C for 2 h. The specific surface area (S) and specific micro-mesopore volume (V) of the original and heated samples were evaluated from N2 adsorption and desorption data, respectively, by standard methods. The adsorption of n-butylamine from the solution in cyclohexane on the samples was used to determine the total surface acidity (nm) and the adsor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 56 publications
6
24
1
Order By: Relevance
“…As compared to the initial sample, the micro-and mesopore volumes reduce by 86.7% and 83.8% respectively, and its micro-and mesopore surface areas reduce by 50.1% and 71.3% respectively, when it is matured to the VRo value of 4.19 %. The result is in agreement with the heating treatment of clay minerals [41,42]. Noyan et al [42] observed an overall trend of decline in both specific surface areas and micromesopore volumes with increasing heating temperature from100 to 900°C for Hancili bentonite from Turkey.…”
Section: Response Of Pore Structure Parameters To Thermal Maturitysupporting
confidence: 83%
“…As compared to the initial sample, the micro-and mesopore volumes reduce by 86.7% and 83.8% respectively, and its micro-and mesopore surface areas reduce by 50.1% and 71.3% respectively, when it is matured to the VRo value of 4.19 %. The result is in agreement with the heating treatment of clay minerals [41,42]. Noyan et al [42] observed an overall trend of decline in both specific surface areas and micromesopore volumes with increasing heating temperature from100 to 900°C for Hancili bentonite from Turkey.…”
Section: Response Of Pore Structure Parameters To Thermal Maturitysupporting
confidence: 83%
“…However, several different results have been obtained by other studies. For example, using a titration method, Mahmoud et al (2003) found that the largest number of acid sites and the highest-strength acid sites appeared after heating at 250°C on Jordanian bentonite, whereas Noyan et al (2006) proposed that the acidity of bentonite declined with increasing temperature (from 25 to 900°C) and found that the highest number of solid acid sites obtained was only 0.45 mmol/g, which is significantly lower than the value obtained in our study. The variation in these results is attributed to the specific features of different montmorillonite samples and the different acidity measurement methods used.…”
Section: Acidity Of Heated Montmorillonitecontrasting
confidence: 91%
“…ions (Lewis acid sites) result from the rupture of Si-O-Al bonds or dehydroxylation at high temperatures (Bhattacharyya and Gupta 2008), and the Lewis acid sites that result from dehydroxylation are of significantly high acid strength Fig. 4 The total number of acid sites of Mt and its heated (a) and cation-exchanged (b) products (determined by n-butylamine titration in nonaqueous system) (Noyan et al 2006). The abnormally low Q L values of Mt-400 and Mt-600 in this study may be explained by the difficulty in detection due to the size of pyridine and the reduction in interlayer spacing, which both prevent basic probes from entering the interlayer to react with unsaturated Al 3?…”
Section: Acidity Of Heated Montmorillonitementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the S BET values of Mt-400 and Mt-600 reflect only their external surface areas. In light of the fact that the layered structure was retained in Mt-400 but destroyed in Mt-600 by heating (Noyan et al, 2006), the measured S BET of Mt-400 could accurately represent the external surface area of Mt without the interference of adsorbed water.…”
Section: Discussionmentioning
confidence: 99%